Efforts To Increase Learning Math Levels With Realistic Math Learning (Pmr) For Student Class V Min Bukit Kubu Beres - Syamsul Bahri (Jurnal Usia Dini, 2017)
This study aims to improve students' mathematics learning outcomes of grade V SD MIN Bukit KubuBesitang, through Realistic Mathematics Approach. This type of research is a classroom action research (PTK). This research uses Kemmis and Mc model. Taggart. The study was conducted in two cycles. Data of research result obtained from test result of student learning, observation result during learning activity using observation sheet of teacher activity in applying Realistic Mathematics Approach, student activeness observation sheet, and documentation. Data analysis techniques used qualitative and quantitative analysis. The results showed that the results of learning mathematics students of grade V SD MIN Bukit Kubu. This is supported by the use of the Realistic Mathematical Approach which emphasizes the 8 aspects with regard to the effectiveness of the number of objects analyzed and the time for learning. Increasing the percentage of student learning outcomes for each cycle, ie on the first cycle of 65.52%, and for the second cycle of 86.21%. In addition, the average percentage of observation sheets of students' mathematics learning activity for each cycle, ie in cycle I of 42.28% and for the second cycle of 73.57%.